The relationship between atherosclerotic disease and relapse during ATD treatment - Zhu, Xinxin; Zhang, Yaguang; Zhao, Xiaoyu; Zhang, Xiaona; Ru, Zixuan; Wu, Yanmeizhi; Yang, Xu; Hou, Boyu; Qiao, Hong (Frontiers in Cardiovascular Medicine, 2022)
Background Clinical relapse is a potential risk for traditional antithyroid drug (ATD) treatment in hyperthyroid patients. Evidence suggests that atherosclerotic disease is closely associated with hyperthyroidism, while the relationship between atherosclerosis and relapse remains unclear. Methods Two hundred and twenty-five patients with GD who underwent ATD as their first treatment were studied; 88 and 137 patients were categorized as drug reduction relapse and drug reduction remission, respectively. Logistic regression was used to analyze risk factors of drug reduction relapse in patients with GD. Results During a median of 48 months followed up 88 patients who relapsed. According to multivariate analyses, atherosclerosis related diseases, FT4, goiter, and anxiety rating scores are independent risk factors for drug reduction. According to K-M survival analysis, patients with atherosclerosis related diseases, FT4 > 18.82 pmol/L, anxiety rating scores > 23, and gradation of goiter ≥ Grade II had a higher risk of relapse than those with lower levels. ROC analysis shown atherosclerosis related diseases significantly improved the predictive accuracy of relapse. Conclusions Atherosclerotic disease is closely related to the relapse of hyperthyroidism, ATD treatment in hyperthyroid patients with atherosclerosis should be given more attention.